2019
DOI: 10.1136/medethics-2018-105120
|View full text |Cite
|
Sign up to set email alerts
|

Pressure in dealing with requests for euthanasia or assisted suicide.Experiences of general practitioners

Abstract: The majority of Dutch physicians feel pressure when dealing with a request for euthanasia or physician-assisted suicide (EAS). This study aimed to explore the content of this pressure as experienced by general practitioners (GP). We conducted semistructured in-depth interviews with 15 Dutch GPs, focusing on actual cases. The interviews were transcribed and analysed with use of the framework method. Six categories of pressure GPs experienced in dealing with EAS requests were revealed: (1) emotional blackmail, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…‘Influencing the public opinion’ has also been mentioned in the Discussion summary as a recommendation of recent research (further education of the general public). 48 This theme was considered important by the experts as the public’s opinion is coloured and misinterpreted about multiple aspects related to euthanasia and dementia, such as ‘euthanasia is a right’, ‘dementia necessarily means suffering’, and a negative perception of nursing homes. Furthermore, an important topic and category within this theme in the present study was ‘legislation clarification’, including the value of an AED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Influencing the public opinion’ has also been mentioned in the Discussion summary as a recommendation of recent research (further education of the general public). 48 This theme was considered important by the experts as the public’s opinion is coloured and misinterpreted about multiple aspects related to euthanasia and dementia, such as ‘euthanasia is a right’, ‘dementia necessarily means suffering’, and a negative perception of nursing homes. Furthermore, an important topic and category within this theme in the present study was ‘legislation clarification’, including the value of an AED.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent interview study with GPs who had experienced pressure around dealing with euthanasia requests in general, the risk of crossing their own personal boundaries if not being able to stand up for their own values was reported, for which education and support were recommended. 16 A recent qualitative study on Dutch physicians’ experiences in dealing with euthanasia requests of PWD confirmed this experienced pressure. 17 GPs experience problems with communication, pressure from relatives, patients, society, workload, interpretation of the law, and ethical considerations.…”
Section: Introductionmentioning
confidence: 93%
“…Lessons from other countries with longer histories with assisted dying may also help to navigate processes and promote smooth care management plans. [38][39][40] The concerns of participants that initiating MAiD discussions may unduly influence patient deci sions echo international findings. In Vermont, where clinicians have an affirmative duty to inform patients of the assisted dying option, some HCPs chose not to initiate discussions due to worries about sending problematic messages, influencing patients' decisions, and damaging therapeutic relationships.…”
Section: Implications For Practice and Policiesmentioning
confidence: 81%
“…Lessons from other countries with longer histories with assisted dying may also help to navigate processes and promote smooth care management plans. 38 40 …”
Section: Discussionmentioning
confidence: 99%
“…Should the eligibility criteria be broadened to include this population, as recently recommended by the Groupe d'experts sur la question de l'inaptitude et l'aide médicale à mourir (2019), efforts will be needed to ensure that patients who requested MAID prior to losing capacity, and meet the yet-to-be-defined legal requirements, can indeed receive assistance in dying. Equally important will be finding ways of supporting health care professionals confronted with such requests and ensuring that none are pressured "to cross their own personal boundaries" (de Boer et al, 2019;Georges et al, 2008;Snijdewind, van Tol, Onwuteaka-Philipsen, & Willems, 2018). As pointed out by Silvius et al (2019), "An overall shift in health care to patient-centred care and the recognition of patient autonomy as a preeminent value has … created the impetus for legalization of MAID practices."…”
Section: Discussionmentioning
confidence: 99%